Impact of virtual education on students in the health sciences area after the SARS-CoV-2 pandemic - Zambrano-Galván, Graciela (2022)
Coronavirus disease 2019 (COVID-19) is a highly communicable acute respiratory infection, which has been declared a pandemic by the World Health Organization. In accordance with government policies for health prevention and social isolation, the virtuality of the entire education system was approved, including careers with a strong practical component such as health sciences; which led to the adaptation of study plans and programs, as well as the immersion of the use of virtual platforms, generating a discovery of new forms of learning both in the theoretical and practical areas, however, at the same time, certain repercussions were generated in practical and psychomotor skills and abilities; also opening a gap between inequality in access to technologies.